2011
DOI: 10.1088/0960-1317/21/7/074007
|View full text |Cite
|
Sign up to set email alerts
|

A single-mask thermal displacement sensor in MEMS

Abstract: Position sensing in MEMS is often based on the principle of varying capacitance [1].Alternative position sensing principles include using integrated optical waveguides

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 23 publications
1
31
0
Order By: Relevance
“…The CV mode is widely reported in the literature. However, the study reported in [3] indicated that the CC excitation leads to a higher sensitivity. Achieving higher resolution is critical for MEMS displacement sensors.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…The CV mode is widely reported in the literature. However, the study reported in [3] indicated that the CC excitation leads to a higher sensitivity. Achieving higher resolution is critical for MEMS displacement sensors.…”
mentioning
confidence: 94%
“…In order to heat up the resistors, electrical power is delivered either by a constant current (CC) [3] or a constant voltage (CV) source [4]. The CV mode is widely reported in the literature.…”
mentioning
confidence: 99%
“…In a first production run a proof of the sensor principle was given [48,72]. In this production run a SOI wafer with device layer 25 ñm, oxide layer 1 ñm and doping concentration 4.7 × 10 18 cm −3 was used.…”
Section: Designmentioning
confidence: 99%
“…The stage is suspended by folded flexures to constrain the movement of the stage to a straight line and to prevent the stage from pull-in due to lateral forces generated by the electrostatic actuators [124,80]. Feedback is provided by a thermal displacement sensor that we have published before [73]. Each sensor consists of two silicon heaters that are resistively heated by applying a fixed voltage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation